Dealing with the impact of the COVID-19 outbreak: Are some athletes` coping profiles more adaptive than others? - Pété, E.; Leprince, C.; Lienhart, N.; Doron, J. (European Journal of Sport Science, 2022)
The public health policies and sanitary measures taken by governments in various countries to stem the spread of the COVID-19 pandemic (e.g., lockdown, social distancing) have major implications for athletes. The radical changes are challenging and risk causing significant career disruption to athletes, with subsequent negative psychological effects. Thus, the ways athletes cope with such adversity is of critical importance. The present study aimed to identify athletes` coping profiles using a person-centred approach, based on their reported use of multiple coping strategies in response to the impact of the COVID-19 outbreak, and to compare levels of anxiety, stress appraisals, interpersonal coping strategies, and availability and appreciation of the major sources of support across profiles. A total of 526 French athletes competing at national to elite levels answered an online questionnaire during the lockdown. Latent profile analysis results yielded four distinct coping profiles (i.e., self-reliant, engaged, avoidant, active and social). The MANOVA showed that athletes belonging to the four profiles differed on anxiety, stress appraisals, social support, and interpersonal coping. In particular, avoidant copers reported high levels of anxiety, threat, and uncontrollability, and appeared less able to regulate responses to the impact of the COVID-19 outbreak. Using a person-centred approach, the findings could inform the development of more adequate care, support, and intervention for athletes, especially avoidant copers, who were characterized by the least effective coping skills and resources. Accordingly, stress reappraisal and stress mindset interventions could be promising approaches to effectively manage pandemic-related impact during and after the COVID-19 crisis.